Inflamed benign tumors of the parotid gland: Diagnostic pitfalls from a potentially misleading entity - Mantsopoulos, Konstantinos; Psychogios, Georgios; Agaimy, Abbas; Künzel, Julian; Zenk, Johannes; Iro, Heinrich; Bohr, Christopher (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2015)
The purpose of this study was to evaluate our experience in the diagnostic approach to inflamed benign tumors of the parotid gland at a single tertiary center.A retrospective evaluation was carried out for all patients with signs of inflammation in the parotid gland on the ground of a benign parotid tumor, as confirmed by permanent histology.Sixteen patients were detected for our study. Histopathologic examination confirmed cystadenolymphoma in 11 cases (with metaplastic changes in 2 cases), 2 pleomorphic adenomas, 2 monomorphic adenomas, and 1 oncocytic cystadenoma. Diverse clinical signs (inflammation signs, facial palsy), ultrasound and MRI findings (poorly defined lesion margins), and the presence of squamous metaplastic changes on cytology often raised the suspicion of parotid malignancy or abscess.In most cases, a high suspicion index combined with close monitoring of the patient may allow prompt and successful diagnosis and therapy. © 2014 Wiley Periodicals, Inc. Head Neck 37: 23-29, 2015.
EVALuna2:6639